First Evidence of Anoxia and Nitrogen Loss in the Southern Canary Upwelling System. Issue 5 (1st March 2019) - Machu, E.; Capet, X.; Estrade, P. A.; Ndoye, S.; Brajard, J.; Baurand, F.; Auger, P.‐A.; Lazar, A.; Brehmer, P.
Abstract: The northeastern Atlantic hosts the most ventilated subsurface waters of any eastern boundary upwelling system, while coastal upwelling source waters are slightly above hypoxic levels. Anoxic conditions have previously been found offshore inside mesoscale eddies whose core waters undergo oxygen consumption for many months. Based on circumstantial in situ observations, this study demonstrates that the Senegalese coastal ocean is subjected to episodic occurrence of zero dissolved oxygen concentration at depth along with elevated nitrite concentration (11 mmol/m 3 ) and nitrate/nitrite deficit to phosphate, thereby indicating severe anoxia and intense nitrogen loss. The anoxic event was associated with a prolonged upwelling relaxation episode in March 2012 and a nearshore diatom bloom that underwent degradation while being advected offshore in stratified waters. This is consistent with scenarios observed in other upwelling systems (Benguela and California), and such conditions are presumably frequent in the southern part of the Canary system. Plain language summary: Oxygen is a key requirement for respiration by marine living organisms. Warming of the atmosphere and the ocean surface reduces the oxygenation of offshore waters. Similarly, the extra load of nutrients from agriculture or waste waters modifies algal production, particularly in coastal regions, often resulting in oxygen‐depleted waters. Specific reactions affecting the ionic forms of nitrogen also occur within oxygen‐depleted waters, which also impact the nitrogen cycle by generating nitrite, which is poisonous for marine organisms, and nitrous oxide, a powerful greenhouse gas. We took measurements at sea to show that a poorly studied coastal sector of the North Atlantic Ocean, the Senegalese continental shelf, can be episodically subjected to complete depletion of subsurface oxygen (anoxia) as well as high nitrite concentrations, constituting the first report of anoxia for this oceanic region. We also show that this anoxia is likely the consequence of the decay of a bloom of diatoms, a group of microalgae common in this type of ecosystem that initially developed in shallow waters and transported offshore by anomalous currents associated with low‐wind conditions. Key Points: Nearshore anoxia was detected in the West African shelf despite subsurface waters being more oxygenated than in other eastern boundary systems Production of nearshore anoxia events in Senegalese waters involves 3‐D dynamics and is plausibly favored during upwelling relaxations Nearshore anoxia has potential implications on the nitrogen cycle through fixed nitrogen loss as observations confirm in Senegalese waters